Plate 5 from Amphitheatrum Sapientiae Aeternae, Solius, Verae [Amphitheatre of the Only True Eternal Wisdom] - Khunrath, Heinrich (Amphitheatrum Sapientiae Aeternae Solius Verae, 1609)
Plate 5 of Khunrath Heinrich's (1560-1605) Amphitheatrum Sapientiae, purportedly one of the most significant books of theosophical alchemy and the occult sciences. Though the title page reads 1602, the book was not published until 1609. Erasmus Wohlfahrt edited and published the manuscript following Heinrich's death in 1605. Wohlfahrt also added a preface and conclusion. The work contains masterful engravings, remarkable for their execution as well as alchemical symbolism. Nine double-paged copperplate engravings, a title page, and a frontispiece can be found in the digital collections. A circular engraving. Within several concentric rings heavily filled with text, a square is outlined. The square contains imagery of a holy book, stone tablets, and text written in a triangular form. At the center, a two-headed figure speaks.
Keywords: Alchemy; Alchemy in art; Alchemy--Religious aspects; Christian art and symbolism; Engraving--Printing; Occultism; Theosophy